Effects of intraspecific larval competition on adult longevity in the mosquitoes Aedes aegypti and Aedes albopictus - REISKIND, M. H. (2009)
Larval competition is common in container-breeding mosquitoes. The impact of competition on larval growth has been thoroughly examined and findings that larval competition can lead to density-dependent effects on adult body size have been documented. The effects of larval competition on adult longevity have been less well explored. The effects of intraspecific larval densities on the longevity of adults maintained under relatively harsh environmental conditions were tested in the laboratory by measuring the longevity of adult Aedes aegypti (L.) and Aedes albopictus (Skuse) (Diptera: Culicidae) that had been reared under a range of larval densities and subsequently maintained in high- or low-humidity regimes (85% or 35% relative humidity [RH], respectively) as adults. We found significant negative effects of competition on adult longevity in Ae. aegypti, but not in Ae. albopictus. Multivariate analysis of variance suggested that the negative effect of the larval environment on the longevity of Ae. aegypti adults was most strongly associated with increased development time and decreased wing length as adults. Understanding how larval competition affects adult longevity under a range of environmental conditions is important in establishing the relationship between models of mosquito population regulation and epidemiological models of vector-borne disease transmission.